Tax audits and the policing of corporate taxes: Insights from tax executives - Seidman, Jeri K.; Sinha, Roshan K.; Stomberg, Bridget (Contemporary Accounting Research, 2025)
We interview public company tax executives to provide new evidence on how corporate taxpayers experience and navigate the income tax audit process. Interviewees describe being “targeted” by “tax police” and having to “defend” their positions. Thus, we adopt a structural metaphor of tax audits as police investigations and use a framework from the policing literature to explain what influences taxpayers' perceptions of fairness during audits. Perceptions of fairness are important as targets of investigations are more likely to cooperate and accept outcomes when they perceive policing processes as fair. Tax executives aim to obtain fair and consistent treatment by compiling documentation, consulting with peers and external advisors, and educating tax agents. Audits are adversarial, however, and taxpayers also act strategically to secure favorable outcomes and appeal or litigate when they believe outcomes are unfair. Interviewees note variation in the extent to which tax authorities create frameworks that facilitate fair audit processes and whether tax agents implement these frameworks. Our study offers new insights into the tax audit process from corporate taxpayers' perspectives. First, public company taxpayers view tax audits as redundant to financial statement audits of their tax positions. Thus, tax audits may have limited scope to deter tax noncompliance. Second, tax executives are not passive actors; they take deliberate actions to shape audit outcomes. Third, audits are less efficient for everyone when taxpayers perceive them as procedurally unfair. Investments by tax authorities that increase perceptions of fairness may enhance audit efficiency by increasing taxpayers' cooperation and acceptance of outcomes.